"La Carne es la Tierra": microcosmic Adam, cartographic Christ in the Libro de Alexandre. Issue 1 (2nd January 2020) - Riva, Fernando
ABSTRACT: This article studies the relationship between the medieval cartographic tradition of Adam's acrostic and the Libro de Alexandre . In particular, it analyzes the Adamic octipartite literature as the point of departure to understand Alexander the Great's flight in apocalyptic terms and the anthropomorphic figure he sees from above.